Scientometric analysis of the development of domestic dissertation research containing the category of «continuous education» in their titles - P. P. Pivnenko; T. N. Poddubnaya; N. P. Vitenko (Вестник Майкопского государственного технологического университета, 2025)
Introduction. The problem of the research is connected with the constant change of the life rhythm caused by technocratic innovations. The neeed for new skills is today an integral component of a multifaceted life in a rapidly changing society. In this regard, the issues of continuous education carry a deep meaning of the objective variability of human life in the context of a dynamically changing reality.Materials and methods. The research methodology is based on the use of a set of methods of scientific knowledge: analysis, classification, systematization, comparison, generalization. Dissertation studies on Pedagogy, the title of which contains the category «continuous education», coducted in the period from 2000 to 2022, served as an empirical base.The Research results. Based on the data obtained through scientometric analysis of dissertation studies, the specified semantic units of the studied scientific and pedagogical content have been recorded; thematic clusters containing in the title significant areas of scientific and practice-oriented topics on the problem of continuous education have been determined.Discussion and conclusion. The evolution of the scientific direction «continuous education» has been revealed, quantitative indicators of its state, the degree of development and demand for pedagogical practice have been determined. An objective picture of the development of this scientific direction has been obtained and its prospects as a subject of scientific and pedagogical discourse ahave been determined.